Simulation of long waves in a layered Sabang waters. (December 2018) - Iskandar, T; Haditiar, Y; Setiawan, I; Fahmi, K; Muhammad, M; Rizal, S
Abstract: Long waves in the waters of Sabang are simulated with a 1-dimensional layered model. The model is discretized with Δx = 3 seconds or approximately 92.5 meters and Δz = 15 meters. The time interval (Δt) is determined based on the CFL criteria. Depth data is obtained from SRTM15 data. The motivation of this research is to study the dynamics of long wave and the dynamics of seawater layer interface which has various density. As the input, it is given the sinusoidal wave with amplitude 2 m and 12 hour period in the open boundary. From the simulation results it is known that the displacement of the interface is about -11 meters to 1.1 meters, while the horizontal current speed is about -1 cm/s to 3 cm/s.